THU0330 Obesity in psoriatic arthritis: comparative prevalence with skin psoriasis and associated factors. (12th June 2018) - Queiro, R.; Lorenzo, A.; Pardo, E.; Brandy, A.; Alonso, S.; Alperi, M.; Arboleya, L.; Ballina, J.
Abstract : Background: Obesity (BMI ≥30 kg/m 2 ) is a common cardiovascular risk factor in psoriatic disease 1 . Although the prevalence of obesity is high, the factors associated with it in psoriatic arthritis (PsA) are poorly understood. Objectives: We aimed to evaluate the prevalence and obesity-associated factors in patients with PsA. Methods: Retrospective cross-sectional study that included 205 consecutive patients with PsA according to CASPAR criteria. The prevalence of obesity was compared with that of 310 patients with skin psoriasis of similar age (±3 years). The factors associated with obesity were first analysed by a conditional logistic regression. The significant factors in this first model were then introduced in a multivariate model using a backward step approach (p-values<0.05 were considered significant). Results: One-hundred twelve men and 94 women were included, with a mean age of 53±13 years. Obesity was more prevalent among psoriatics (36.5%) compared to PsA patients (24%), OR 1.6 (1.1–2.3), p<0.05. The factors associated with obesity in the univariate analysis (p<0.05) were: onset of psoriasis >40 years (OR 2.4), onset of arthritis >40 years (OR 2.1), PsA family history (OR 3.1), polyarticular presentation (OR 1.9), axial presentation (OR 2.5), polyarticular evolution (OR 2.4), axial evolution (OR 4.2), diabetes (OR 3.6), HBP (OR 3.9), and dyslipidemia (OR 3.5). After correcting for age, sex, disease duration and other confounders, independent associations with obesity found in the multivariate model (p<0.05) were: PsA family history (OR 3.6, IC95%: 1.1–14.4), axial evolution (OR 4.4, IC95%: 1.0–22.4) and dyslipidemia (OR 3.5, IC95%: 1.5–8.6). Conclusions: Obesity was more common among our patients with cutaneous psoriasis than in those with arthritis. The model that best explains obesity in this PsA series combines genetic factors (PsA family history), together with factors specific to the metabolic syndrome (dyslipidemia), with others owned to arthritis (axial evolution). Reference: [1] Husni ME. Comorbidities in psoriatic arthritis. Rheum Dis Clin North Am2015;41:677–98. Disclosure of Interest: None declared